2009
DOI: 10.1111/j.1467-8683.2009.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Codes of Good Governance

Abstract: Manuscript Type: ReviewResearch Question/Issue: We review the recent developments in the area of codes of good governance, a set of best practice recommendations regarding the behavior and structure of the board of directors. Research Findings/Results: Our review of the literature on codes of good governance highlights their rapid spread around the world and how academic research has lagged behind in analyzing this topic. Despite the criticism that the codes' voluntary nature limits their ability to improve go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
244
0
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(266 citation statements)
references
References 47 publications
11
244
0
11
Order By: Relevance
“…It is contended, however, that in developing countries with different cultural, regulatory, CG, and institutional contexts, such as Saudi Arabia (Aguilera & Cuervo-Cazurra, 2009), voluntary compliance with CG Codes can be expected to vary from what has been found in developed countries. Therefore, an investigation of voluntary CG disclosures in developing countries, where there is a dearth of empirical evidence, is crucial in offering a more complete understanding of CG reforms and disclosure behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is contended, however, that in developing countries with different cultural, regulatory, CG, and institutional contexts, such as Saudi Arabia (Aguilera & Cuervo-Cazurra, 2009), voluntary compliance with CG Codes can be expected to vary from what has been found in developed countries. Therefore, an investigation of voluntary CG disclosures in developing countries, where there is a dearth of empirical evidence, is crucial in offering a more complete understanding of CG reforms and disclosure behavior.…”
mentioning
confidence: 99%
“…Generally, and notwithstanding the increasing number of CG Codes in developing countries, such as Saudi Arabia (Aguilera & Cuervo-Cazurra, 2009;Samaha et al, 2012), existing studies investigating the effectiveness of voluntary CG Codes in improving governance standards are disproportionately concentrated in a few developed countries (Bebenroth, 2005;Bozec & Bozec, 2007;Cromme, 2005;Hooghiemstra, 2012;Hussainey & Al-Najjar, 2012;Mallin & Ow-Yong, 2012;Pass, 2006;Pellens, Hillebrandt, & Ulmer, 2001;Salterio et al, 2013;Werder et al, 2005). It is contended, however, that in developing countries with different cultural, regulatory, CG, and institutional contexts, such as Saudi Arabia (Aguilera & Cuervo-Cazurra, 2009), voluntary compliance with CG Codes can be expected to vary from what has been found in developed countries.…”
mentioning
confidence: 99%
“…What this shows is that in countries where there is power distance, institutional owners seem to have strong influence over credit rating (Aguilera and Cuervo-Cazurra, 2009). This influence is widely accepted in countries where power distance is a way of life.…”
Section: Descriptive Analysis and Bivariate Correlationsmentioning
confidence: 99%
“…An explanation for this could be that the majority of the countries in which the corruption index was high demonstrated that it affected credit rating. Since these were also countries in the stakeholding tradition, the European model, the fact that institutional ownership was held by many founder families who made decisions primarily in their interests would also be supposed by owners making decisions for their interests (Aguilera and Cuervo-Cazurra, 2009). …”
Section: Descriptive Analysis and Bivariate Correlationsmentioning
confidence: 99%
“…In addition to this, according to our understanding, this is the first study in treating the application of new regulation on corporate governance in different institutional environments as an explanatory variable in determining the maturity of bank debt contracts across countries. Differently than ours, other papers have focused on diverse aspects of regulation on the firm's financial decisions such as the role of law on corporate self-dealing, the effects of banking liberalization and the adoption of codes of good governance on capital structure (Djankov et al 2008;Aguilera, Cuervo-Cazurra 2009;González 2015, among others). Nevertheless, our paper goes one-step forward in the intuition that changes in the corporate governance laws might influence the maturity in the design of bank debt contracts, and through this, the conduct of managers.…”
Section: Introductionmentioning
confidence: 99%